2019
DOI: 10.1021/acsanm.9b00265
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Passivation and Encapsulation of Black Phosphorus Nanosheets (Phosphorene) by Optically Active Polypeptide Micelles for Biosensors

Abstract: In a simplistic way, 2D black phosphorus (BP) nanosheets are exfoliated in a polar solvent at room temperature. Afterward, as-obtained BP or phosphorene nanosheets are passivated and encapsulated simultaneously by using an artificial polypeptide polymer having an ability to form micelles. In first step, thin layers of BP nanosheets were obtained by sonication. Next, helical copolymer based on polyethylene glycol and poly(phenyl isocyanidepeptide) blocks is then allowed to blend with the suspension of phosphore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…The outstanding biocompatibility and biodegradability of functionalized BPNSs in physiological environment makes them attractive and promising for wide bioapplications in photodynamic therapy [197] and photothermal therapy, [181,201,250,252,253] tissue engineering, [254,255] biosensors, and bioimaging. [196,202,256,257] Qiu et al have developed a new concept of light activation of BPNSs based hydrogel for cancer therapy. [250] In their approach, BPNSs was prepared by liquid phase exfoliation in isopropanol.…”
Section: Refsmentioning
confidence: 99%
“…The outstanding biocompatibility and biodegradability of functionalized BPNSs in physiological environment makes them attractive and promising for wide bioapplications in photodynamic therapy [197] and photothermal therapy, [181,201,250,252,253] tissue engineering, [254,255] biosensors, and bioimaging. [196,202,256,257] Qiu et al have developed a new concept of light activation of BPNSs based hydrogel for cancer therapy. [250] In their approach, BPNSs was prepared by liquid phase exfoliation in isopropanol.…”
Section: Refsmentioning
confidence: 99%
“…Kumar [48], for the first time, applied a simple and yet useful strategy to combine 2D phosphorene and an artificial helical copolymer (a polypetide), chemically engineered for its architecture and supramolecular assembly. The helical polymer provides several advantages: (1) it passivates and encapsulates BP nanosheets, (2) it electronically interacts with the BP nanosheets, (3) it can allow the fabrication of inorganic BP nanosheets for their integration in devices without sacrificing the inherent properties of BP nanosheets, and (4) it protects BP nanosheets from atmospheric oxygen.…”
Section: Functionalization Of Phosphorenementioning
confidence: 99%
“…It is evident that there is a considerable lack of experimental investigations for the functionalization of arsenene, antimonene, and bismuthene. Noncovalent coatings of BP with organic molecules include electrostatic interactions, vdW interactions, charge‐transfer mechanism, and hydrogen bonding …”
Section: Surface Functionalizationmentioning
confidence: 99%
“…In a novel strategy, an artificial or fabricated polypeptide polymer was used for encapsulation and passivation of phosphorene nanosheets . The helical copolymer with the ability to form micelles was obtained by polyethylene glycol and poly(phenyl isocyanidepeptide) blocks ( Figure ) . It was suggested that BP nanosheets encapsulated and passivated inside the polymeric micelle through the charge‐transfer mechanism .…”
Section: Surface Functionalizationmentioning
confidence: 99%
See 1 more Smart Citation